The status of Callianira hexagona (Slabber, 1778) (Ctenophora) - Bennema, F.P. & G.W.N.M. van Moorsel (Zool. Med. Leiden, 2011)
In 1768, Martinus Slabber collected the only specimen ever found of the ctenophore species mostly cited as Callianira hexagona (Slabber, 1778). After analysing the international confusing literature on this species, we conclude the nomenclatural correct name should be Callianira slabberi De Haan, 1827. The designation to Callianira was done by 19th-century taxonomists, who did not realize that Slabber’s drawing lacks most of the transparent outer part of the animal, as indicated in the accompanying Dutch text. Moreover, Slabber’s description contains details not consistent with ctenophore morphology. Most probably, Slabber described a juvenile specimen of Pleurobrachia pileus (O.F. Mu¨ller, 1776), and C. slabberi may be considered a junior synoym of the latter species. A copy of Slabber’s drawing has been used in the allocation of another ctenophore species in Callianira. Combined with the fact that this genus was based on a poorly described specimen, this throws doubts on the validity of the genus Callianira.